Generalized Resolvents of Symmetric Relations Generated on Semi-Axis by a Differential Expression and a Nonnegative Operator Function - Bruk, V. M. (Журнал математичної фізики, аналізу, геометрії, 2006)
Generalized resolvents of a minimal symmetric relation generated on the semi-axis by a formally selfadjoint differential expression and a nonnegative operator function are described.Mathematics Subject Classification: 47A06, 47A10, 34B27.